Germinal center kinase-like kinase (GLK/MAP4K3) expression is increased in adult-onset Still's disease and may act as an activity marker - Chen, Der-Yuan (BioMed Central, 2012)
BACKGROUND: Germinal center kinase-like kinase (GLK, also termed MAP4K3), a member of the MAP4K family, may regulate gene transcription, apoptosis and immune inflammation in response to extracellular signals. The enhanced expression of GLK has been shown to correspond with disease severity in patients with systemic lupus erythematosus. We investigated the role of GLK in the pathogenesis of adult-onset Still's disease, which shares some similar clinical characteristics with systemic lupus erythematosus. METHODS: The frequencies of circulating GLK-expressing T-cells in 24 patients with active adult-onset Still's disease and 12 healthy controls were determined by flow cytometry analysis. The expression levels of GLK proteins and transcripts were evaluated in peripheral blood mononuclear cells by immunoblotting and quantitative PCR. Serum levels of T helper (Th)17-related cytokines, including IL-1β, IL-6, IL-17 and TNF-α, were measured by ELISA. RESULTS: Significantly higher median frequencies of circulating GLK-expressing T-cells were observed in patients with adult-onset Still's disease (31.85%) than in healthy volunteers (8.93%, P <0.001). The relative expression levels of GLK proteins and transcripts were also significantly higher in patients with adult-onset Still's disease (median, 1.74 and 2.35, respectively) compared with those in healthy controls (0.66 and 0.92, respectively, both P <0.001). The disease activity scores were positively correlated with the frequencies of circulating GLK-expressing T-cells (r = 0.599, P <0.005) and the levels of GLK proteins (r = 0.435, P <0.05) or GLK transcripts (r = 0.452, P <0.05) in patients with adult-onset Still's disease. Among the examined Th17-related cytokines, elevated levels of serum IL-6 and IL-17 were positively correlated with the frequencies of circulating GLK-expressing T-cells and the levels of GLK proteins as well as transcripts in patients with adult-onset Still's disease. GLK expression levels decreased significantly after effective therapy in these patients. CONCLUSIONS: Elevated expression levels of GLK and their positive correlation with disease activity in patients with adult-onset Still's disease indicate that GLK may be involved in the pathogenesis and act as a novel activity biomarker of this disease.